2016
DOI: 10.1093/molbev/msw037
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Genetic Modeling ofpfcrt-Mediated Drug Resistance Evolution inPlasmodium falciparum

Abstract: The emergence of drug resistance continuously threatens global control of infectious diseases, including malaria caused by the protozoan parasite Plasmodium falciparum. A critical parasite determinant is the P. falciparum chloroquine resistance transporter (PfCRT), the primary mediator of chloroquine (CQ) resistance (CQR), and a pleiotropic modulator of susceptibility to several first-line artemisinin-based combination therapy partner drugs. Aside from the validated CQR molecular marker K76T, P. falciparum par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 108 publications
(162 reference statements)
5
85
0
Order By: Relevance
“…In addition, several novel PfCRT mutations have been observed that can revert parasites to a CQ-sensitive status despite the presence of K76T, including C101F—which arose under pip-eraquine (PPQ) or amantadine pressure in vitro 42,166 —or C350R, which has recently spread throughout French Guiana 167 . Some PfCRT variants also mediate resistance to the active metabolite of AQ (monodesethyl-AQ), which might have been an important driving force for selection 168,169 . Importantly, all mutant CQ-resistant pfcrt alleles known so far increase P. falciparum susceptibility to lumefantrine, both in vitro and in field settings, and often increase sensitivity to ART derivatives, benefiting the clinical efficacy of the first-line ACT AL 170172 .…”
Section: Multidrug Resistance (Mdr)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several novel PfCRT mutations have been observed that can revert parasites to a CQ-sensitive status despite the presence of K76T, including C101F—which arose under pip-eraquine (PPQ) or amantadine pressure in vitro 42,166 —or C350R, which has recently spread throughout French Guiana 167 . Some PfCRT variants also mediate resistance to the active metabolite of AQ (monodesethyl-AQ), which might have been an important driving force for selection 168,169 . Importantly, all mutant CQ-resistant pfcrt alleles known so far increase P. falciparum susceptibility to lumefantrine, both in vitro and in field settings, and often increase sensitivity to ART derivatives, benefiting the clinical efficacy of the first-line ACT AL 170172 .…”
Section: Multidrug Resistance (Mdr)mentioning
confidence: 99%
“…Most mutant pfcrt alleles come with a fitness cost, indicated in the field by a decrease in their allelic prevalence in the absence of CQ pressure 177 , and in vitro as reduced growth rates when compared to recombinant isogenic parasites expressing the wild-type allele 35,169,178 . Reduced fitness might involve less efficient Hb catabolism and peptide transport in PfCRT mutants, as well as other digestive-vacuole-related physiological processes 178,179 .…”
Section: Multidrug Resistance (Mdr)mentioning
confidence: 99%
“…Among CQ-resistant field isolates, PfCRT isoforms are comprised of geographically distinct clusters of single-nucleotide polymorphisms (SNPs), namely K76T and 3 to 8 additional point mutations. PfCRT K76T is a critical, albeit insufficient, determinant of parasite in vitro CQR [16]. This mutation also predicts in vivo CQ treatment failure with high sensitivity but lower specificity [17].…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, PfCRT is a multi-pass transporter embedded in the intra-erythrocytic parasite’s digestive vacuole (DV) membrane, with enigmatic functions that may include transport of ions and/or peptides [1821]. In the absence of PfCRT structural information, mutational approaches have guided studies into the effect of specific PfCRT mutations on drug transport and parasite growth [16,2224]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation